Experience of using zonisamide in children in routine clinical practice (a multicenter study) - M. Yu. Bobylova; I. V. Volkov; O. K. Volkova; I. S. Bakhtin; D. I. Gukosyan; O. A. Rakhmanina; M. V. Barkhatov; I. G. Shchukina; Yu. Yu. Kalinina; K. Yu. Mukhin (Русский журнал детской неврологии)
Background. The problem of antiepileptic therapy in children remains highly relevant due to the insufficient efficacy of standard drugs, adverse events, and limitations of clinical guidelines.Aim. To assess the efficacy, tolerability, and continuation of zonisamide (Zonegran) therapy in children with epilepsy.Materials and methods. This retrospective multicenter study was conducted in epileptology centers in various regions of the Russian Federation, including Moscow, Novosibirsk, Krasnodar, Tyumen, Krasnoyarsk, Voronezh, Ryazan). We included 340 patients under the age of 18 (202 boys and 138 girls) with various epileptic syndromes receiving zonisamide (mean age was 10.63 years). Zonisamide was administered to patients with the following epileptic syndromes: age-dependent self-limited focal epilepsy of childhood (n = 49; 14 %) structural focal epilepsy (n = 102; 30 %), focal epilepsy of childhood with structural brain changes and benign epileptiform discharges of childhood visualized at electroencephalography (n = 38; 11.2 %), idiopathic generalized epilepsy (n = 23; 6.7 %), developmental and epileptic encephalopathies (n = 44; 12.9 %) (including developmental and epileptic encephalopathies with spike-and-wave activation during sleep (n = 23; 6.7 %)), Lennox–Gastaut syndrome and infantile epileptic spasms syndrome (n = 32; 9.4 %), genetic epilepsy with generalized and focal seizures (n = 81; 23.8 %). The type of the seizures was distributed as follows: focal motor (n = 205), bilateral tonic-clonic (n = 192), generalized (n = 197), including generalized convulsive (n = 44), tonic (n = 70), atonic (n = 2), myoclonic (n = 26), epileptic spasms (n = 36), absence seizures (n = 19). One patient could have more than one type of seizures. Magnetic resonance imaging demonstrated some changes in 185 patients, whereas 117 patients had no magnetic resonance imaging changes. Thirty-eight patients did not undergo magnetic resonance imaging as they had no indications to it. The most common structural epileptogenic changes were the consequences of perinatal lesions manifesting as cystic-gliotic transformation, atrophy (125 cases in total); less common changes included focal cortical dysplasia, developmental abnormalities (such as polymicrogyria, lissencephaly, holoprosencephaly), mesial temporal sclerosis, and tumors. Zonegran (zonisamide) as an additional therapy was administered at a dose of 3–8 mg/kg/day (mean dose 5 mg/kg/day) to 321 patients.Results. Zonegran (zonisamide) therapy was effective in 257 (75.6 %) of patients; remission was achieved in 174 patients (67.7 %), while reduced seizure frequency (50 % and greater) was registered in 83 patients (32.3 %). A total of 72 patients (21.2 %) reported no adverse events. Twenty participants (5.8 %) had some adverse events; in 4 cases, they were resolved after dosage decrease; in 16 cases, treatment with zonisamide was discontinued.Conclusion. Zonegran (zonisamide) is effective for comprehensive treatment of both focal and generalized epilepsy in children*.